2015
DOI: 10.1021/nl503641c
|View full text |Cite
|
Sign up to set email alerts
|

Strain Shielding from Mechanically Activated Covalent Bond Formation during Nanoindentation of Graphene Delays the Onset of Failure

Abstract: Mechanical failure of an ideal crystal is dictated either by an elastic instability or a soft-mode instability. Previous interpretations of nano-indentation experiments on suspended graphene sheets [1,2], however, indicate an anomaly: the inferred strain in the graphene sheet directly beneath the diamond indenter at the measured failure load is anomalously large compared to the fracture strains predicted by both soft-mode and acoustic analyses. Through multi-scale modeling combining the results of continuum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
5
19
0
Order By: Relevance
“…As shown in Fig. 21, both large and small hydrogen (Kumar and Parks 2015). a Illustration of the indenter surface with varying hydrogen saturations.…”
Section: Other Fracture Modes In Graphenementioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Fig. 21, both large and small hydrogen (Kumar and Parks 2015). a Illustration of the indenter surface with varying hydrogen saturations.…”
Section: Other Fracture Modes In Graphenementioning
confidence: 97%
“…With multi-scale analysis combing quantum, MD and FEM simulations, Kumar and Parks (2015) investigated the failure of graphene under nano-indentation, focusing on mechanochemical interactions at the graphene-indenter interface. Based on ab initio and MD simulations, they showed that covalent bonding between graphene and certain crystallographic facets on a diamond indenter can form under the compressive contact stresses during indentation.…”
Section: Other Fracture Modes In Graphenementioning
confidence: 99%
“…This method relies on the fact that the physical and mechanical properties of materials are functions of elastic strain [Gilman, 2003] and they also depend on the symmetry of crystal lattice, that can be altered by elastic strain. Nanomaterials such as thin films, nanowires, nanopillars and atomic sheets can withstand ultra-high stresses without plasticity or fracture [Zhu and Li, 2010;Kumar and Parks, 2015]. Consequently, the elastic strain level achievable in nanomaterials can be 100 times larger than in the macroscopic materials.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of sp 2 -hybridized carbon atoms and demonstrates outstanding stretchability, up to about 20-30%, without being damaged [Kumar and Parks, 2015;Dmitriev et al, 2012;Liu et al, 2007;Lee et al, 2008;Baimova et al, 2012a]. This makes graphene perfect for ESE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation